ANALISIS PENDETEKSIAN POTENSI RESIKO KECURANGAN LAPORAN KEUANGAN MELALUI PERSPEKTIF FRAUD PENTAGON (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia - Nona Prabavatica SE (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to predict and explain the effect of pentagon fraud elements on the detection of potential financial statement fraud risks. The pentagon fraud element is proxied by five variables, pressure, opportunity, rationalization, capability, dan arrogance. Potential financial statement fraud risk as the dependent variable is proxied by an F-Score. Of 342 non-financial sector companies listed on the IDX, 35 companies are at risk of conducting financial statement fraud in the form of misstatement (fraud risk). Using the sample using the matched pairs design method, one fraud risk company is paired with one non-fraud risk company based on certain criteria. Data analysis was performed by binary logistic regression using SPSS software. The results of this study indicate that pressure affect the detection of potential financial statement fraud risks. While opportunity, rationalization, capability, dan arrogance does not affect the detection of potential financial statement fraud risk. Keywords: Fraud Pentagon, Pressure, Opportunity